(3fbO GdCQGA GdefWbjI hMd eTcdGJgGs - (3GdfLaj, GHf cGTa GdZWGA, Ydj Hf eMeO QVG Hf ehSi, J HYO (B1354(3g`s
(3ChdgG (B:s
(3ChdgG(B: (3GdbVjI, JYQja GdbVjI, YQa GdefWbjhf GdbVjI HCfgG(B: (3bhd jMJed GdUOb hGdcPH hjQO Ydjge NeSI YTQ EjQGOGs
(3BNQgG (B:s
(3BNQgG(B: (3hLhGHgG(B: (3Ef GdeWdb gfG gh GdeYOhe CYe ef Cf jchf faSg Ch LSeg Ch fXjQg hgh UGOb Ydjg bWYG hEfeG GdPj dG jUOb Ydjg gh GdeYOhe faSg hgh djS HeWdb Hd gh ebjO fXjQ GdGYOGe GdeJbOes
(3JHUQI GdeDda (B:s
(3PcQ GdRQcdj haGJg SfI (B1350(3g`, ZjQ Cfg cGf MjG SfI (B1354(3, hab eG PcQg eG PcQ aj fgGjI GdLRA GdYGTQ ef cJGH TQM GdcaGjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B5: 19s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3GdadSaI hGdefWbs